1996
DOI: 10.1080/00140139608964497
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic offending, stress, age, and accident history among male and female drivers

Abstract: This paper draws on data gathered during a larger study of driving behaviour to explore possible connections between stress, offending against the traffic laws, and accident rates, and gives particular attention to comparisons between male and female drivers. Data were gathered from 422 drivers by a postal questionnaire, and further measures of stress were obtained during semi-structured interviews with a specially selected subset of 66 of them. Analyses of variance investigated links between offending rates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(68 citation statements)
references
References 21 publications
4
48
1
9
Order By: Relevance
“…More work to explore the gender gap could repay attention, though as noted earlier, women's and men's driving styles are not assumed to be without overlap and a better understanding especially of those women who tend to adopt male driving styles (e.g. Reason et al, 1990;Simon and Corbett, 1996) would also be useful and interesting.…”
Section: Control Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More work to explore the gender gap could repay attention, though as noted earlier, women's and men's driving styles are not assumed to be without overlap and a better understanding especially of those women who tend to adopt male driving styles (e.g. Reason et al, 1990;Simon and Corbett, 1996) would also be useful and interesting.…”
Section: Control Explanationsmentioning
confidence: 99%
“…Indeed, earlier research suggests that some women have distinctive styles. For instance, Reason et al (1990) reported that around 10% of female drivers aged 36 or more were high violators and Simon and Corbett (1996) found that some career women admitted to similar levels of speeding and other road offending as men. In this context too, it is relevant to consider current claims about the emergence of a 'ladette culture' among younger women such that increasing aggression on the road and the adoption of a deviant masculine driving style, including drink-driving, is becoming more evident among them (e.g.…”
Section: Table 1 About Herementioning
confidence: 99%
“…The implication is that good drivers are more likely to avoid accidents than are drivers with a record of offending. According to Simon and Corbett (1996), results of accident history are positively related to offending. The number of accidents and offences is higher among young men and their index of accidents is higher than those of women or older drivers (Laapoti et al, 2001;Yahya and Hammarstroöm, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is therefore based on the assumption that there exists a particular group of collisions in which one of the drivers involved (the one who committed an infraction) is more responsible than the other driver(s), or is more likely to be the responsible driver than are the drivers who committed no infraction (15). Although the relationship between committing an infraction and the risk of being involved in traffic crashes has been well established (20)(21)(22), the assumption that the infractor is responsible for the collision may not be true. However, the approach we used in the present study makes such an association plausible: in a collision in which only one of the drivers committed an infraction and the other involved drivers did not, the former driver is much more likely to have caused the accident (15).…”
Section: Methodological Considerationsmentioning
confidence: 99%